The Health Care Provider's Role in Securing Work Accommodations for Pregnant and Postpartum Patients . (25th August 2020) - Franco, Juliana; Morris, Liz; Lee, Jessica; Williams, Joan C.
Abstract : Most women today are the primary, sole, or cobreadwinners for their families; their continued ability to work during and after pregnancy is crucial for their families' well‐being. Midwives and other health care providers are regularly asked to provide work notes for patients who need adjustments to how, when, or where their job is done to continue working while maintaining a healthy pregnancy or breastfeeding. Whereas an improperly written work note can result in the patient being forced out on leave or losing their job, an effectively written work note from a health care provider can ensure the patient will receive the adjustments they need to stay safe and healthy on the job. Health care providers can also play an important role by incorporating discussions about workplace issues into care conversations. This article provides an overview of pregnancy‐related employment rights, guidelines for writing effective work notes, and a discussion of common workplace issues patients face and how health care providers can respond.